2022
DOI: 10.1039/d2tb00484d
|View full text |Cite
|
Sign up to set email alerts
|

Grafting resveratrol onto mesoporous silica nanoparticles towards efficient sustainable immunoregulation and insulin resistance alleviation for diabetic periodontitis therapy

Abstract: The treatment of diabetic periodontitis (DP) has become a tough challenge in dental clinic mainly due to the intrinsic drawbacks of conventional therapy strategy and currently unclear mechanisms to elucidate...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 80 publications
0
12
0
Order By: Relevance
“…Furthermore, silibinin up‐regulated the level of phosphorylated cAMP response element‐binding protein (p‐CREB) (Li et al, 2018), which directly induced PGC‐1α transcription (Song et al, 2020). More importantly, studies have shown that Sirt1 (Tan et al, 2022), AKT (Kim et al, 2022) and p‐CREB (Abidi et al, 2020) are involved in the development of periodontitis. Therefore, under the condition of DP, Sirt1, AKT and p‐CREB might be involved in the modulatory effect of silibinin on PGC‐1α.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, silibinin up‐regulated the level of phosphorylated cAMP response element‐binding protein (p‐CREB) (Li et al, 2018), which directly induced PGC‐1α transcription (Song et al, 2020). More importantly, studies have shown that Sirt1 (Tan et al, 2022), AKT (Kim et al, 2022) and p‐CREB (Abidi et al, 2020) are involved in the development of periodontitis. Therefore, under the condition of DP, Sirt1, AKT and p‐CREB might be involved in the modulatory effect of silibinin on PGC‐1α.…”
Section: Discussionmentioning
confidence: 99%
“…Tan et al designed a resveratrol (RSV)-graft mesoporous silica nanoparticle (MSN) drug carrier system and discovered that MSNs regulated the polarization of macrophages by inhibiting the NF-kB signaling pathway and facilitated the transition from M1 to M2 phenotypes. 66 The results demonstrated that MSNs can reduce the expression of pro-inflammatory factors and enhance the release of anti-inflammatory factors, thereby reducing bone resorption and the destruction of periodontal tissues.…”
Section: Introductionmentioning
confidence: 93%
“…In response to stimuli of the classical pathway, such as periodontal bacterial products and massive recruitment of pro-inflammatory cytokines, activation of IκB kinases (IKKα and β, and the regulatory subunit IKKγ) phosphorylates IκBα and inhibits serine residues 65 within the amino-terminal structural domain of the protein and induces its ubiquitination and degradation by proteases, which subsequently enter the nucleus and activate transcription of specific pro-inflammatory genes. 66,67 Despite its functional adaptability in response to inflammatory stimuli, dysregulation of NF-κB signaling has been found in various disease states where NF-κB activity promotes sustained inflammatory signaling at the molecular level, thereby exacerbating periodontal inflammation leading to soft tissue destruction and bone resorption and even atherosclerosis. 68 It has been reported that inhibiting NF-κB signaling promotes M2 polarization and reduces inflammation.…”
Section: Immune Cell Activation and Participation In The Progression ...mentioning
confidence: 99%
“…Resveratrol (RSV; 3,5,4’-trihydroxy-trans-stilbene) has strong anti-inflammatory and antimicrobial effects, but its application is severely constrained by the poor water solubility, rapid decomposition, and short serum half-life ( Bhattarai et al., 2016 ). The RSV-grafted MSN drug carrier could successfully extend its bioavailability in the local periodontal region, resulting in sustained pharmacological activity and removing RSV’s inherent cytotoxicity ( Tan et al., 2022 ). For RSV’s anti-inflammatory effects and the ability to modulate glucose metabolism, MSN-RSV may also be able to alleviate diabetic periodontitis (DP) ( El-Makaky and Shalaby, 2020 ).…”
Section: The Prospective Application Of Mesoporous Silica Nanoparticl...mentioning
confidence: 99%